2019
DOI: 10.1039/c9sc00793h
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the π-bridge of quadrupolar triarylborane chromophores for one- and two-photon excited fluorescence imaging of lysosomes in live cells

Abstract: The tetracationic diketopyrrolopyrrole compound 5M exhibits a σ2 value of 4560 GM at 740 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
76
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 139 publications
4
76
0
Order By: Relevance
“…We recently reported the water-soluble and stable cationic bis-triarylborane derivative 1 as an ew fluorophore applicable for one-and two-photon excited fluorescence imaging in cells. [3] Given that only af ew examples of water-soluble triarylboranes have been reported to date, [4][5][6][7][8][9][10][11][12][13] such borane-based chromophores could be considered to be novel fluorophores for biochemical applications;t hey are already widely used in nonlinearo ptical materials, organic electronics, organic lightemitting diodes or anion sensors. [14][15][16][17][18][19][20][21][22] However,f luorescence of 1 only enabled intracellularl ocalisation of ad ye, but did not allow fort he determination of at argeted biomacromolecule (for example, protein or DNA or RNA).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the water-soluble and stable cationic bis-triarylborane derivative 1 as an ew fluorophore applicable for one-and two-photon excited fluorescence imaging in cells. [3] Given that only af ew examples of water-soluble triarylboranes have been reported to date, [4][5][6][7][8][9][10][11][12][13] such borane-based chromophores could be considered to be novel fluorophores for biochemical applications;t hey are already widely used in nonlinearo ptical materials, organic electronics, organic lightemitting diodes or anion sensors. [14][15][16][17][18][19][20][21][22] However,f luorescence of 1 only enabled intracellularl ocalisation of ad ye, but did not allow fort he determination of at argeted biomacromolecule (for example, protein or DNA or RNA).…”
Section: Introductionmentioning
confidence: 99%
“…Previously,i tw as observed that the solventp olarity has a large influence on the two photon cross-section value. [22] Therefore, the two-photon absorption (TPA) cross-section of (M,M,M,P,P,P)-3 was measured in two solvents with al arge differencei np olarity,T HF,a nd toluene, via two-photoni nduced fluorescencer elative spectroscopict echnique ( Figure 6). The observedo verlap between one-and two-photon absorption spectra is,o no ne hand, attributed to the noncentrosymmetric molecule, in which the parity selection rule does not hold.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of air-stable conjugated three-coordinate organoboron compounds have been synthesized over the last few decades [1][2][3][4][5][6][7][8] for various applications, particularly in linear [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and nonlinear [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] optics, electro-optic devices, [40][41][42] anion sensors, [43,44] cell imaging, [45][46][47][48] etc. The boron center in these species possesses an empty p-orbital and can thus serve as a strong π-acceptor following photo-excitation, or as a readily reducible center.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative bulky groups with higher electron affinities should enhance acceptor strength while maintaining or even enhancing the desired chemical stability of the systems. [6,12,28,[36][37][38][57][58][59][60][61][62][63][64][65][66][67] Exploiting this favorable property, some of us recently reported a series of air-stable bis (fluoromesityl)boryl ((FMes) 2 B) derivatives, namely compounds 1-3 (Scheme 1) with different electron-donating groups for comparison, i. e., phenyl, 4-tert-butylphenyl and 4-N,N-diphenylaminophenyl, respectively, attached to the electron acceptor group (FMes) 2 B through BÀ C bonds. [12] Comparison of these (FMes) 2 B-containing donor-acceptor compounds with compound 4, which contains a (Mes) 2 B group (Scheme 1), confirms that (FMes) 2 B is a much stronger acceptor, leading to: (i) a larger quinoidal distortion in the ground state structure; (ii) significantly red-shifted emission in solution and in the solid state; (iii) stronger emission solvatochromism; and (iv) significantly lower reduction potentials.…”
Section: Introductionmentioning
confidence: 99%